Performance Effects of Working Capital in Emerging Markets - Alshammari, Turki (International Journal of Economics and Financial Issues, 2018)
This paper strives to provide evidence of the effect of working capital policies on corporate profitability in a new and different setting, the Gulf Cooperation Council (GCC) countries. As the corporate private sector receives lavish subsidies from local oil-rich governments, both the theoretical propositions and the worldwide accepted evidence are glitched. Employing a set of pooled regression models, this paper documents a trivial, if any, association between the efficiency of working capital management and the corporate profitability for a set of nonfinancial firms in all the GCC countries. The results are robust to the econometric model, the profitability measure, and the country. Keywords: Working Capital, Tobin’s Q, Debt ratio, Profitability, Cash Conversion Cycle, GCC countries, Firm Value JEL Classifications: G3, G31